Konflik Sosial pada Novel Sisi Tergelap Surga Karya Brian Khrisna (Perspektif Konflik Sosial Ralf Dahrendorf) - Rina Novita Sari; Abdul Kholiq (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the social conflicts found in Brian Khrisna's novel Sisi Tergelap Surga (The Darkest Side of Heaven) based on Ralf Dahrendorf's conflict theory. This study uses a descriptive qualitative method with a literary sociology approach. The data source used is the novel Sisi Tergelap Surga by Brian Khrisna. The data presented in this study are in the form of sentences, paragraph excerpts, and dialogue quotations that contain two faces of society (conflict and consensus), power and authority, conflicting groups, and conflict control. The results of this study show the existence of (1) conflict and consensus, with conflict taking the form of violence, threats, and sexual harassment, while consensus takes the form of agreements and consent formed to achieve peace, (2) power and authority, with power demonstrated through the actions of the village head towards his citizens and authority held by Tomi, (3) opposing groups in the form of pseudo-groups consisting of residents who gather situationally and interest groups consisting of public schools established by Erlin, (4) conflict control in the form of arbitration.